Nonmedical prescription pain reliever and alcohol consumption among cannabis users. (1st February 2016) - Novak, Scott P.; Peiper, Nicholas C.; Zarkin, Gary A.
Highlights: Over time, the prevalence of cannabis increased but pain reliever misuse declined. Over time, poly-drug use involving dual use of cannabis and pain reliever misuse declined Higher levels of cannabis use was positively associated with pain reliever misuse. Abstract: Background: This study examined poly-drug use involving the use of cannabis with nonmedical prescription pain reliever use (NMPR) and alcohol use. Methods: Computer-assisted survey data from the National Survey on Drug Use and Health were examined. The NSDUH is an annual, cross-sectional survey of non-institutionalized citizens in the United States (ages 12+). Replicate analyses were conducted using the 2013 and 2003 survey waves. Results: Higher levels of cannabis use were consistently associated with more frequent consumption of prescription pain relievers, with findings replicating in both 2013 and 2003. While the prevalence of dual users declined from 2003 (2.5%) to 2013 (2.3%), the average number of days used among dual users increased by an average of 20 days over that period. These changes largely occurred among those aged 35 or older, males, whites, and non-illicit drug users. Past-year marijuana use increased by 16% (10.8–12.6%, p -value < .001) whereas NMPR decreased by 15% (4.9–4.2%, p -value < .001). The largest changes occurred after 2011. Persons using the most cannabis generally had higher levels of alcohol use relative to those using the least amount of cannabis. There was a significant increase in the prevalence of dual use between 2003 (10.2%) and 2013 (11.6%), while the prevalence of past-year alcohol use remained relatively stable. Conclusions: Clinical efforts and public health interventions should consider the possible co-ingestion of cannabis with NMPR and alcohol, as concomitant use may portend negative health effects in the short and long-term.